Ocular damages inflicted by criminal injuries - T. V. Gavrilova; N. A. Sobyanin; A. V. Patrushev; M. V. Chereshneva (Российский офтальмологический журнал, 2022)
Purpose: to analyze eyeball and appendage damages inflicted by criminal injuries of patients who sought assistance by the emergency ophthalmological care unit in Perm.Materials and methods. The data of the patients’register and medical histories of the ophthalmological department of the State Clinical Hospital No. 2 named after Dr. F. H. Gral of Perm for 2018–2020 were retrospectively analyzed.Results. Out of 30428 cases of domestic injuries, 847 (2.8%) were received under criminal circumstances. The victims, predominantly male (77.6%), and of working age (93.7%), were delivered by ambulance in 51.6% of cases. The majority of people sought assistance within 24 hours (90%). The injuries were inflicted by strangers (59.5%) or acquaintances of the patients. 1257 eyes were injured. The prevailing conditions were contusions (46.9%), while the most common traumatizing factor was first punch (79.6%). Combined damages to the eyeball and appendage were more common, claiming 72.6%. Visual acuity fell below 0.1 in 5.6% of cases, 0.1–0.6 in 57.6%, 0.7–1.0 in 36.8% of cases. 45.9% of all cases were represented by eye burns: mainly they were chemical burns (99.5%) of which the overwhelming type was burns caused by gas spray irritants (97.9%). In burn cases, visual acuity was below 0.1 in 1.4% of cases, 0.1–0.6 in 62.6%, 0.7–0.8 in 36% of cases. The wounds inflicted to the eye amounted to 7.2%, the damaging factors being handgun bullet, glass, metallic objects. Injuries of the eyelids and the eyeball were observed. Most of the injuries were mild (91.3%). 5.83% of the victims needed hospitalization in an ophthalmological in-patient facility.Conclusion. The eye trauma, especially one of a criminal nature, is a social problem, and its analysis is highly relevant. The data obtained illustrates the need to increase the general culture of the population, to improve sanitary and educational work, and optimize medical care for those suffered.